2015
DOI: 10.1021/acs.chemmater.5b00187
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Induced Formation of Monodisperse Hydrogel Nanoparticles Tunable in Size

Abstract: We report a novel approach to synthesize monodisperse hydrogel nanoparticles that are tunable in size. The distinctive feature of our approach is the use of a multicopper oxidase enzyme, laccase, as both a biocatalyst and template for nanoparticle growth. We utilize the ferroxidase activity of laccase to initiate localized production of iron(III) cations from the oxidation of iron(II) cations. We demonstrate that nanoparticles are formed in a dilute polymer solution of alginate as a result of cross-linking bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Enzymatic reactions can be used to produce Fe 3+ -Alg monodisperse nanoparticles. 80 Multi-copper oxidase enzyme laccase greatly accelerates the oxidation of Fe 2+ to Fe 3+ by dissolved oxygen. If the reaction is conducted in the presence of sodium alginate the reluctant Fe 3+ cations are instantly trapped by alginate chains near the enzyme molecule producing a Fe 3+cross-linked shell around it growing with nearly constant rates for every enzyme molecule.…”
Section: Hydrogel Synthesis Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymatic reactions can be used to produce Fe 3+ -Alg monodisperse nanoparticles. 80 Multi-copper oxidase enzyme laccase greatly accelerates the oxidation of Fe 2+ to Fe 3+ by dissolved oxygen. If the reaction is conducted in the presence of sodium alginate the reluctant Fe 3+ cations are instantly trapped by alginate chains near the enzyme molecule producing a Fe 3+cross-linked shell around it growing with nearly constant rates for every enzyme molecule.…”
Section: Hydrogel Synthesis Strategiesmentioning
confidence: 99%
“…Enzymatic reactions can be used to produce Fe 3+ -Alg monodisperse nanoparticles. 80 The electrodeposition conditions were optimized for a graphite electrode at 35 mM Fe 2+ , 1.5% (w/v) NaAlg and 0.8 V (vs. Ag|AgCl) for 60 seconds. 47 It should be noted that the required applied potential might be different for electrodes made of different materials or with chemically modified surfaces.…”
mentioning
confidence: 99%
“…Here, the chelation effects between polysaccharides and metal ions have been utilized for the preparation of enzymatically cross‐linked nanogels ( Figure a). Bocharova et al prepared a monodisperse, alginate‐based nanogel with tunable size using laccase as both a template and catalyst . First, biocompatible alginate was electrostatically adsorbed around a laccase core.…”
Section: Molding Process Of Micro/nanogels and Hydrogelsmentioning
confidence: 99%
“…a) Enzyme‐mediated radical cross‐linked micro/nanogels were created based on the chelation effects between polysaccharides and metal ions and laccase‐induced oxidation of iron(II) to iron(III), and b) laccase‐mediated radical cross‐linked polysaccharide GCS. a) Reproduced with permission . Copyright 2015, American Chemical Society.…”
Section: Molding Process Of Micro/nanogels and Hydrogelsmentioning
confidence: 99%
“…Horseradish peroxidase (HRP) has been utilized to prepare hydrogels via HRP-mediated oxidative coupling of phenol and aniline derivatives with the aid of hydrogen peroxide (H 2 O 2 ). However, few studies on enzymatically cross-linked nanogels were reported. Bocharova et al utilized laccase as both a biocatalyst and template and fabricated alginate nanogels . Haag and co-workers fabricated cross-linked dendritic polyglycerol (dPG) nanogels by HRP-catalyzed oxidative cross-linking of phenolic derivatized dendrimer in an inverse miniemulsion, and the dPG nanogels provided efficient scaffolds for active protein encapsulation .…”
mentioning
confidence: 99%